PECULIARITIES OF POLICE PROFESSIONAL TRAINING IN THE EUROPEAN UNION (END OF THE XX - BEGINNING OF THE XXI CENTURY - Сергій Білявець (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2021)
The article presents the results of the analysis of regulatory and scientific sources, which reveal the features of police training for EU countries at the end of the 20th and the beginning of the 21st centuries. It was found that the integration of European states in the second half of the 20th century and the first decade of the 21st century contributed to the fact that the system of police training was changing in accordance with the changes in the political and socio-economic situation in individual EU countries and in the Community as a whole. The police training system itself is part of the integration processes within the framework of the integration of the EU law enforcement and police systems. Features such as the practical orientation of training, its continuous nature, and its close relationship to practice are characteristic of all police training institutions in EU countries. At the same time, EU countries are ambivalent about the innovations proposed by the 1999 Bologna Convention. States with established educational systems (Austria, Belgium, Cyprus, Denmark, France, Germany, Luxembourg, Malta, the Netherlands, Portugal, Sweden, and the United Kingdom) are more conservative and less inclined to abandon their own educational standards, unlike Eastern European states that pursue radical reform policies, including reforms in police training. In police education programs, a significant number of hours are devoted to the development of skills and abilities to work with scientific and technological means, which are extremely widely used in police work in foreign countries. It was also found that police officers are thoroughly and comprehensively prepared for close interaction of national services, both through Interpol and directly with each other. At conferences, symposiums, seminars, exchanges of experience and delegations, increased attention is certainly given to police training.